Non-formal education of children and youth as a sociosphere of developing the creative potential of society - Yakovleva, Irina A. (Journal of the Belarusian State University. Sociology, 2023)
The article deals with theoretical and methodological approaches to establishing the imperative of creativity as the basis for the economic and socio-cultural development of network societies in the 21st century. A description of the scientific reflection of the processes of evolution of economic and social systems in the direction of the formation of creative economies is given. The formation of successful life strategies of an individual, as well as the social potential and effectiveness of the collective action of generational cohorts, are due to the essential characteristics of post-industrial societies developing in a situation of civilisational challenges of global instability. There is a growing social need to rethink the classical paradigms of education and expand the social field for the application of variable and flexible social technologies in education, which make it possible to implement personally directed education models and form an individual educational strategy. The evolution of educational systems in the direction of personal motivating education is considered. The paper analyses current trends in the transformation of the value paradigm of the ideology of education, based on the formation of universal competencies of the future, among which modern educational strategies focus on the development of metasubject and personal competencies, as well as on mastering the skills of systemic thinking. The sociocultural phenomenon of additional education is considered as a sociosphere that includes both the institutional characteristics of an educational organisation and informal sociocultural practice, public self-organisation and amateur creative and civic initiatives. Additional non-formal education is considered as a social mechanism for implementing the strategy of mobile continuous education, which is personalised throughout life.
Keywords: additional education; creativity; creative economy; life strategy; competencies of the 21st century; personal education; continuous education; cultural creativity; sociosphere